Tools for Making a Decision at the Planning Phase of Housing Development Project - Zainal, Rozlin; Mohd Sofberi, Nurul Atiqah; Mohd Noh, Hamidun (International Journal of Sustainable Construction Engineering and Technology, 2022)
Literature discovered that the selection of the right tool affects the decision-making process at the planning phase of housing development project. Imprecise decision-making are capable of generating big threat to project completion. Therefore, the adoption of the right tool by decision makers are compulsory to prevent the occurrence of any difficulties on the final stage of the project. The objective of this research is to define the decision-making tool applied at the planning phase of housing development project in Malaysia. A total of 80 sets of structured questionnaires were distributed to the private housing developers in Malaysia and out of 67 were found usable after data screening. The descriptive statistical analysis and the correlated analysis are conducted in this study aided by Statistical Package for Social Sciences (SPSS) software. The results of this study show that most of the Malaysian private housing developers applied potential analysis, comparison analysis, economic analysis, feasibility study and 4P’s analysis as tools when making a decision at the planning phase of housing development project. Hence, this paper is supposed to lead the potential private housing developers along with the governments by providing a number of tools in making decisions at the planning phase of housing development project in Malaysia.